Imagery-focused cognitive therapy (ImCT) for mood instability and anxiety in a small sample of patients with bipolar disorder: a pilot clinical audit - Hales, SA; Di Simplicio, M; Iyadurai, L; Blackwell, SE; Young, K; Fairburn, CG; Geddes, JR; Goodwin, GM; Holmes, EA (Cambridge University Press, 2018)
Background: Despite the global impact of bipolar disorder (BD), treatment success is limited. Challenges include syndromal and subsyndromal mood instability, comorbid anxiety, and uncertainty around mechanisms to target. The Oxford Mood Action Psychology Programme (OxMAPP) offered a novel approach within a cognitive behavioural framework, via mental imagery-focused cognitive therapy (ImCT). Aims: This clinical audit evaluated referral rates, clinical outcomes and patient satisfaction with the OxMAPP service. Method: Eleven outpatients with BD received ImCT in addition to standard psychiatric care. Mood data were collected weekly from 6 months pre-treatment to 6 months post-treatment via routine mood monitoring. Anxiety was measured weekly from start of treatment until 1 month post-treatment. Patient feedback was provided via questionnaire. Results: Referral and treatment uptake rates indicated acceptability to referrers and patients. From pre- to post-treatment, there was (i) a significant reduction in the duration of depressive episode relapses, and (ii) a non-significant trend towards a reduction in the number of episodes, with small to medium effect size. There was a large effect size for the reduction in weekly anxiety symptoms from assessment to 1 month follow-up. Patient feedback indicated high levels of satisfaction with ImCT, and underscored the importance of the mental imagery focus. Conclusions: This clinical audit provides preliminary evidence that ImCT can help improve depressive and anxiety symptoms in BD as part of integrated clinical care, with high patient satisfaction and acceptability. Formal assessment designs are needed to further test the feasibility and efficacy of the new ImCT treatment on anxiety and mood instability.